TECHNOLOGICAL CLUSTERS AND THEIR ROLE IN DEVELOPMENT OF RF REGIONAL ECONOMICS - V. A. Serguiytchuk; I. M. Yagoudin (Модернизация, инновация, развитие, 2016)
Economic notion «cluster» implies a group of technologically linked companies mutually using their resources to develop and produce competitive products. First Russian innovative infrastructure elements are Business-incubators, Scientific and Technological Centers under higher schools,Technical Parks under major state research centers and Technology Transfer Centers. Decisively important for the development of RF regions are Innovative Technological Clusters (ITC) and cluster groups. ITC structural scheme is recommended. ITC will successfully function provided they areformed under certain geographical, economical and institutional conditions. Purpose-aimed cluster development program, legal instruments and investment fund with state participation should be created.